The components of e-service quality in the e-commerce business / Farzana Afrina Azlan - Azlan, Farzana Afrina (2022)
People can select and buy their desired products at any time by using an e-commerce website. They can easily pay by using credit cards or other payment options on the e-commerce website. There are several difficulties that faced by e-commerce website developer and they needs to consider the problem because it gives great impact in the e-commerce business. To gain better understanding, this research is carried out to identify the components of e-service quality in the e-commerce business and develop e-service quality model. This research is conducted by using the qualitative method. The data in this research are collected by using the interview. The research result presents the findings of the interview session with the customer who has experience in purchase products or service through the e-commerce business. It can be concluded that there are nine components that been identified which are fulfillment, responsiveness, availability, ease of use, assurance, website design, credibility, reliability, and accessibility. The results obtained can be used and important to the e-commerce website developer or future researcher. The e-commerce website developer can use the findings from this research to help them to recognize the areas that need to be improved and components of e-service quality in the e-commerce business. This research also benefits by contributing to a general knowledge of the e-service quality field and enhances the future understanding of e-service quality components in the e-commerce business.